EMPLOYMENT RELATIONSHIP BETWEEN TAUKE AND FISH CULTIVATION OF KERAMBA JARING APUNG (KJA) IN NAGARI KOTO MALINTANG KECAMATAN TANJUNG RAYA KABUPATEN AGAM PROVINSI SUMATERA BARAT - Novyta Karsela; Ridar Hendri; Kusai Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted on 19 June - 03 July 2018 in Nagari Koto Malintang Kecamatan Tanjung Raya Kabupaten Agam Provinsi Sumatera Barat. The purpose of this study was to determine the reason for the establishment of a working relationship, to know the pattern of work relationships and to know the advantages and disadvantages of the relationship between the tauke and KJA fish farmers. The research method used is the Phenomenological Qualitative Method by conducting direct observation and interviewing informants who are guided by the questionnaire. The informant determination technique used is Purposive Sampling which is considered by researchers that the informants have in-depth information and can be trusted to be a solid source of data. The number of informants was 7 people consisting of 2 tauke and 5 fish cultivators. Research results show that the reasons for the establishment of a working relationship are: first, economic factors in meeting the needs of life, secondly, the employment factor and the three factors of kinship. While the pattern of employment relationships are patterns of economic relations, patterns of social relations and patterns of personal relationships. The advantages and disadvantages between tauke and fish cultivator are collateral for borrowing capital for daily needs borrowed by the tauke, but the catch must be sold to the tauke not be sold to other parties. Keywords: Pattern of Employment Relations, Boss, Cultivator, Floating Net Cage